Structure-function relationship of reading performance in patients with early to moderate glaucoma - Akar, Serpil; Tekeli, Oya; Idil, Aysun; Ozturker, Zeynep Kayaarasi (European journal of ophthalmology, 2024)
To assess reading performance in patients with mild to moderate primary open-angle glaucoma (POAG), and to determine the relationship between reading ability and visual field (VF), microperimetry, and optical coherence tomography (OCT) parameters. Reading performance of 30 POAG patients examined by the Minnesota Reading Acuity Chart (MNREAD) was compared to that of 21 age-matched controls collected from Ankara University in Turkey. Humphrey Field Analyzer (HFA) 24-2 SITA Standard and 10-2 patterns, and microperimetry were used for VF measurements. All subjects underwent OCT analysis for retinal nerve fiber layer thickness (RNFLT), optic nerve head (ONH) measurements, and ganglion cell inner plexiform layer thickness (GCIPLT). The linear relationship between reading parameters and VF, microperimetry, and OCT parameters was investigated. Univariate and multiple logistic regression models were used to identify the risk factors for glaucoma. In POAG patients, maximum reading speed (MRS) had a significant association with average rim area, mean cup-to-disc ratio (CDR), and cup volume ( < 0.05, for all). Decreased MRS was associated with thinner average GCIPLT and inferotemporal, superior, and inferior GCIPLT quadrants ( < 0.05, for all). Global index values for the HFA 24-2/10-2 tests, microperimetry, and ONH/RNFLT parameters had no correlation with reading performance. After accounting for the better and worse eyes, gender, education, age, and visual acuity of the glaucoma patients, MRS score was 23 units lower in the worse eye ( = 0.009), critical print size (CPS) was 0.21 units larger in the better eye ( = 0.03) and 0.25 units larger in the worse eye ( < 0.001), reading accesibility index (ACC) was 0.11 units lower in the better eye ( = 0.02) and 0.13 units lower in the worse eye ( = 0.002), and RA was 0.13 units higher in the worse eye ( = 0.003) of POAG patients. POAG had significantly lower reading performance when compared to healthy subjects. Reading speed was associated with decreased macular GCIPLT indicating that reading performance may be affected in the earlier stages of the disease.